Uji Efektivitas Ekstrak Kurma Ajwa, Povidone Iodine 10%, dan Bioplacenton pada Luka Bakar Mencit - Putri A.R., Shafira Nur Afifa; Dwimartyono, Fendy; Lantara, Andi Millaty Halifah Dirgahayu; Syahril, Erlin; Khalid, Nur Fadhillah (Syifa'Medika, 2025)
Burns are tissue damage caused by contact with heat sources and require proper medical treatment. Povidone iodine 10% is often used, however, it can cause irritation and slow healing. This study aimed to evaluate the effectiveness of Ajwa Date Extract (Phoenix dactylifera), Povidone iodine 10%, and Bioplacenton in healing burns in mice (Mus musculus). The research method used a post-test controlled group design  with four treatment groups: control (NaCl 0.9%), Ajwa Date Extract, Povidone iodine 10%, and Bioplacenton. The number of samples used was 24 mice in each of 4 groups, so that 6 mice were obtained in each group. The statistical tests used were the Normality Test and  the Saphiro-Wilk Test  The parameters observed included the duration of healing, infection, and allergic reactions. The results showed that Ajwa Date and Bioplacenton extracts  accelerated wound healing by an average of 11.5 days, faster than Povidone iodine 10% (12 days) and control (13.6 days). All groups showed the same total healing score (8), with no infections or allergic reactions. The Kruskal-Wallis statistical test  showed a significant difference in the duration of healing (p = 0.003). In conclusion, Ajwa Date Extract and Bioplacenton are  effective in accelerating the healing of burns and can be a safe and effective treatment alternative.